Indonesia Cooperative and Members Welfare : a Panel Data Analysis - Lestari Agusalim; Muhamad Karim; Yaddarabullah Yaddarabullah (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
Indonesia Cooperative is believed as the most appropriate institution in increasing the welfare of its members and the society, and also participating to build the national economic in order to create the advanced society, fair, and prosperous society based on Pancasila and the 1945 Constitution of the Republic of Indonesia. In proving, the purpose of this research is to analyze the effect of Indonesia cooperative existence to the welfare of its members. The method of analysis is the data panel regression, where cross section data covers all provinces in Indonesia, and time series data during 2010-2015. The result shows that the main factors that have effect to the members’ welfare are number of members, number of managers, self-capital, and business volume. The variables that have no significant effect to the members’ welfare are numbers of cooperatives, the annual member meeting (AMM), number of employees, outside capital, and macro economy variable in regional level. Economic growth and outside capital variables have indirect effect to the members’ welfare through volume of cooperative business.